Dreamless ebook - Angelini, Josephine (Starcrossed, 2012)
StarHearts, as fans of Josephine Angelini call themselves, will stay up all night reading Dreamless, the second book in the bestselling Starcrossed series. The saga mixes mythology, romance, action, and intrigue in a completely original way. Dreamless continues the story of Helen Hamilton, a shy girl living on Nantucket Island whose desire for an ordinary life was thwarted when she discovered she is a Scion, a descendant of a Greek god and a mortal. Each Scion has a power, and Helen's is the ability to travel to Hades. Helen is determined to use her talent to stop a war amongst the gods and change her destiny, which is to live a life patterned after that of the tragic Helen of Troy. But her quest may cost her Lucas Delios, the boy she loves.